Menggali Etika Pengacara dalam Alquran - Jepry Tarantang (LP2M IAIN Palangka Raya, 2015)
The advocates are the professions (officium nobile) who act law enforcers. The advocates as law enforcers guaranteed by the regulation no. 18 the year 2003 about the advocates are tied with the ethics. The ethics of Indonesian Advocates the year 2002 becomes the guidance for the advocates in performing their professions. However, those advocates who are Muslims, the ethics should be based on the values in the Alquran. The study is classified as explanatory, namely, explaining, strengthening, or examining a regulation related of the ethics of advocates. The results of the analysis concluded that Quran Surah Annisa [4]: 58,105, and 135 as the bases of the ethics of the advocates. The concepts of the ethics in these verses, are, trusteeship and fair, including good behaviors, honesty, responsible, professional, having the skill, having high integrit y in performing professions as law enforcers constitutionally. The ethics of the advocates in the Alquran can be applied by protected the positive law in the form of the collaboration of the ethics based on the qur’anic values and the regulation no. 18 the year 2003 about the Advocates, and the Ethics of the Indonesian Advocates the year 2002.